Correlation Between Chronic Pain Acceptance and Clinical Variables in Ankylosing Spondylitis and Its Prediction Role for Biologics Treatment - Li, Ting; Liu, Yaqun; Sheng, Rong; Yin, Jian; Wu, Xin; Xu, Huji (Frontiers in Medicine, 2020)
Objectives: Studies have proven that improving patients’ acceptance of chronic pain could be an effective therapy for alleviating pain and other symptoms. Our objectives were to investigate the correlation between chronic pain acceptance and clinical variables in ankylosing spondylitis (AS), and the prediction role of chronic pain acceptance for biologics treatment. Methods: First, 167 AS patients were recruited to complete a series of questionnaires, including the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index (BASFI), Chronic Pain Acceptance Questionnaire (CPAQ), Hospital Anxiety and Depression Scale (HADS), and Tampa Scale for Kinesiophobia (TSK). Bivariate correlation analysis was utilized to investigate the correlation between pain acceptance and clinical variables. Based on the level of chronic pain acceptance (CPAQ score) and serum C-reactive protein (CRP), patients were separated into four subgroups. The Kruskal-Wallis test was utilized to compare different variables between multiple subgroups. The Mann-Whitney U test was subsequently used for post hoc analyses. Then, another 68 patients initiating anti-tumour necrosis factor (TNF) treatment were recruited to complete the questionnaires at baseline (T0) and 3 months after treatment (T3). The changes in CRP, CPAQ, BASDAI and BASFI were compared between multiple subgroups Results: Chronic pain acceptance had strong correlations with anxiety, depression and fear of movement, moderate correlations with BASFI and pain severity, and no significant correlations with BASDAI and CRP. Subgroup analysis showed that patients with low chronic pain acceptance and high levels of serum CRP had the highest BASDAI. Among patients initiating anti-TNF treatment, those with high pain acceptance and high levels of serum CRP achieved the most obvious reduction in BASDAI after 3 months treatment. Conclusion: Lower acceptance of chronic pain was correlated with more serious pain severity, higher BASFI and worse psychological status. Clinicians should identify high-risk patients who have low chronic pain acceptance and high levels of serum CRP. Moreover, the combination of baseline chronic pain acceptance and serum CRP level could be used to predict the treatment response in AS patients initiating biologics treatment.